IMPROVING SELF-MANAGEMENT AND INDEPENDENT LEARNING COMPETENCIES IN EDUCATIONAL ACTIVITIES (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
The article explores the development of students’ competencies in self-directed learning and self-regulation in educational activities. Self-directed learning and self-regulation skills help students acquire knowledge effectively, enhance critical thinking, and increase responsibility. Based on the analysis of existing pedagogical sources, the article examines effective methods for developing these competencies in students, including planning, time management, goal setting, reflection, and the use of modern technologies. This approach supports the enhancement of both academic and personal achievements of students.